2006
DOI: 10.1029/2006jg000208
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic assessment of NO3 and SO42− mobility during winter in two adjacent watersheds in the Adirondack Mountains, New York

Abstract: [1] Biogeochemical cycling of N and S was examined at two watersheds in the Adirondack Mountains, New York, to better understand the retention and loss of these elements during winter and spring snowmelt. were observed in forest floor and mineral soil leachates, groundwater, and streams. Over the winter observation period, most of the NO 3 À and SO 4 2À in stream water was from a watershed-derived source, whereas atmospheric contributions were relatively minor. Despite differences in soil water NO 3 À concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 76 publications
(121 reference statements)
6
57
2
Order By: Relevance
“…Principal component analysis (PCA, McHale et al, 2002) focusing on NO 3 sources and isotopic assessments of NO 3 and SO 4 2 (Piatek et al, 2005;Campbell et al, 2006;Mitchell et al, 2006) has been conducted previously at Archer Creek. In addition to multiple stream sampling locations, McHale et al (2002) evaluated the contribution of shallow/deep soil water, shallow/deep wetland pore water, groundwater, and throughfall as potential runoff sources using end-member mixing analysis (EMMA).…”
Section: Methodsmentioning
confidence: 99%
“…Principal component analysis (PCA, McHale et al, 2002) focusing on NO 3 sources and isotopic assessments of NO 3 and SO 4 2 (Piatek et al, 2005;Campbell et al, 2006;Mitchell et al, 2006) has been conducted previously at Archer Creek. In addition to multiple stream sampling locations, McHale et al (2002) evaluated the contribution of shallow/deep soil water, shallow/deep wetland pore water, groundwater, and throughfall as potential runoff sources using end-member mixing analysis (EMMA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous analysis at Arbutus watershed, including estimates of dry deposition, suggested that an internal S source was required to balance the S budget (Park et al 2003). Results using SO 4 2-isotopic evidence (d 18 O and d 34 S) (Campbell et al 2006) and spatial patterns of SO 4 2-concentrations (Piatek et al 2009) have suggested that some subcatchments of the Arbutus Watershed have a strong internal S source. Previous work at Cone Pond has suggested the potential importance of a fire in 1820 that heavily burned 85% of the watershed.…”
Section: Comparisons Of Sulfur Budget Differences Among Watershedsmentioning
confidence: 95%
“…Previous studies have observed increases in stream d 18 O-NO 3 -values during snowmelt indicating modest contributions (up to *35%) to stream NO 3 -directly from melting snow or other precipitation source (e.g., Spoelstra et al 2001;Burns and Kendall 2002;Pardo et al 2004;Piatek et al 2005;Campbell et al 2006;Hales et al 2007 . 6a).…”
Section: Nitrate Loss During the Dormant Seasonmentioning
confidence: 97%